âUse of ICT in Teaching-Learning & Evaluationâ - Yasa, Made Semadi (Jurnal Pendidikan Bahasa, 2012)
The writer of the article explained briefly the history of teaching learning process in India which applied the âGurukul System of Educationâ which were dedicated and knowledgeable teachers, individualized and learner center teaching, and self-motivated students eager to learn. And it moved toward to the use of Audio-Video aids in supporting teaching learning process till the use of ICT as the media in that process. âGurukul System of Education was in vogue in India. The main characteristics of Gurukul System were dedicated and knowledgeable teachers, individualized and learner centre teaching, and self-motivated students eager to learn. This system changed due to increase in number of students. Consequently, the number of teachers increased. Some teachers are born but rests of them have to be given rigorous training so as to develop required competency to become a teacher. Teachers have been conscious about the quality of their teaching. To enhance the quality, some teachers use teaching aids, like, charts, models â static & working, specimen, slides, etc. because teachers are given training both in preparation and use of Audio-visual Aids. It is a known fact that majority of schools do not have appropriate teaching aids related to the school content. So teachers have no facility to use A â V Aids during teaching. . . . . This is the age of INFORMATION dominated by the Digital Technology. The Digital Technology has influenced all aspects of human life. Education is not an exception. . . . . One such device is Computer. The Computer is an electronic device that has the capacity to store, retrieve & process both qualitative & quantitative information fast and accurately. The computers were never developed for improving quality of teaching â learning process. But researchers started using Computers for teaching purpose. It gave birth to Computer Assisted Instruction (CAI), Computer Managed Instruction (CMI), Computer Based Instruction (CBI), etc. People started developing CAI for teaching different subjects at School as well as Higher Education level.â